2018
DOI: 10.1016/j.supflu.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A green desuperheater for an energetic efficient alternative to the decompression valve in biomass supercritical water ultrafast hydrolysis process

Abstract: The supercritical water hydrolysis (SCWH) of biomass (P=250bara & T=400ºC) allows directly obtaining sugars, which are high value products in the chemical industry, in reaction times lower than 0.2s. The process is characterized by the high selectivity values which can be obtained controlling the reaction time. Reaction kinetics show that glucose degradation is only retarded at temperatures below 250ºC. Therefore, in the traditional SCWH process, degradation control is achieved expanding the hydrolysis stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The first solution is to further concentrate the product using a flash separator . The second solution is to use a so-called desuperheater instead of a needle valve to stop the reaction, which can in theory lower the temperature while keeping the pressure high, thus limiting the energy loss during depressurization …”
Section: Results and Discussionmentioning
confidence: 99%
“…The first solution is to further concentrate the product using a flash separator . The second solution is to use a so-called desuperheater instead of a needle valve to stop the reaction, which can in theory lower the temperature while keeping the pressure high, thus limiting the energy loss during depressurization …”
Section: Results and Discussionmentioning
confidence: 99%
“…In a 301 previous study, both processes were compared for sugar cane bagasse hydrolysis and it was 302 concluded that SCW technology allowed reducing the total investment of the biorefinery 303 and the water intake (Albarelli et al, 2017). Moreover, several alternatives were proposed 304 to improve the energetic efficiency of the FASTSUGARS process, from the coupling of the 305 ultrafast reactors to commercial combined heat and power (CHP) systems (Cantero et al,306 2015c) to the use of a green desuperheater as an alternative to decompression valve 307 (Vaquerizo & Cocero, 2018). So that, the improved yields obtained in the case of SBP and 308 the lower cost associated to SCW technology, proved that FASTSUGARS process is a 309 promising and versatile technology to convert biomass into sugars in a sustainable way.…”
Section: 2liquid Product Characterization 206mentioning
confidence: 99%
“…It is possible to reduce the operation cost by improving the energy and work recovery, for example, by recovering the work associated with the depressurization, and implementing energy integration [39].…”
Section: Scw Process Perspectivesmentioning
confidence: 99%